PERANCANGAN APLIKASI E-FOODCOURT DENGAN TEKNOLOGI AUGMENTED REALITY BERBASIS WEB - Nurlaila; Ellbert Hutabri (LPPM Universitas Putera Batam, 2024)
With technological developments in various fields that influence human life, one of which is the culinary field. However, when showing the food and drink menu from a foodcourt, there aro no props available to display the menu. Currently, when showing food and drink menus to customers, only 2D images are used. By utilizing augmented reality technology, it is hoped that it can help foodcourt in presenting food and drink menus to make them more attractive because augmented reality can be a tool to display menus in 3D form. By using 3D visuals, it is also hoped that it can help customers to know more about the menus available at the foodcourt. With augmented reality supported by the markerless method, the foodcourt can display the available menus in 3D as well as details of each menu. In modelling 3D objects about the menus, software in the form of Blender will be used. For system development, the prototype method will be used so that the steps of development are known.